Planejamento, síntese e avaliação da atividade tipo ansiolítica e do perfil antioxidante de novo candidato a protótipo de fármaco LQFM 180 - Braga, Patrícia Caixeta Castro Souza (2016)
Faced with the high and increasing number of people suffering from some form of mental illness in the world, it is necessary to develop additional therapeutic options for patients not helped by existing treatments and also to address medical / famacológicas unmet needs. Given this panorama, this paper proposes the design, synthesis and evaluation of pharmacological type anxiolytic activity and antioxidant profile of a new drug candidate prototype 4- (3,5-ditert-butyl-4-hydroxybenzyl) piperazine-1 carboxylate acetate (LQFM180 (8)). The new prototype was designed by molecular hybridisation strategy of prototypes from 4 - ((1-phenyl- 1H-pyrazol-4-yl) methyl) piperazine-1-carboxylate Ethyl (LQFM008 (5)) and 2,6-di- tertbutyl-phenol (BHT (9)). LQFM180 (8) The compound was synthesized by the Mannich reaction, in 92% yield, which was chemically characterized by infrared spectroscopy (IR) and nuclear magnetic resonance dimensional and two-dimensional (1H, HSQC and HMBC). Evaluation of antioxidant status was carried out by cyclic voltammetry, which confirmed that the compound has antioxidant activity. For evaluation central pharmacological activity of the compound were worked four behavioral models in animals, with treatment with LQFM180 at doses of 25, 50 and 100 mmol / kg V.O. In the test of sleep induced by sodium pentobarbital, the LQFM180 (8) reduced latency and increased barbiturate sleep duration, indicating a central depressant activity. Treatment with LQFM180 (8) in different doses did not alter the number of self-cleaning, dung, total and raised intersections, behavioral parameters observed in the open field test; there is no impairment of exploratory activity. Also in the open field test, the compound LQFM180 (8) indicated anxiolytic type activity, demonstrated by the increase in length of stay, and the entrance in the center of the field. LQFM180 (8) treatment did not alter the motor activity test in the chimney, which was evidenced by the animal climbing time. The compound LQFM180 (8) evaluated the maze test in high cross, possess anxiolytic activity type; evidenced by the increase in time and entering the open arms and the time reduction in the central platform. At the end of this work we can see that the synthetic route proposed for obtaining LQFM180 (8) compound was effective, given the high yields obtained, little laborious steps and cost. Finally, we conclude that the employee structural planning was ratified before the success of the structural characterization of the compound and the results obtained from the central pharmacological evaluation in animal models. As perspective, it is necessary to establish the mechanism of action of the molecule as well as the continuation of in vivo evaluations.